2019
DOI: 10.5897/ajmr2019.9065
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antibiotic resistance profiles of bacteria from influent, effluent and downstream: A study in Botswana

Abstract: Antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) have been globally considered environmental contaminants that pose a serious problem to the health of humans, animals and the ecosystem. The primary objective of the study was to characterize the antibiotic resistance phenotypes and genotypes of bacterial isolates from Gaborone wastewater treatment plant (GWWTP) and the downstream environment receiving effluent wastewater. Culture dependent and independent approaches were used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…At baseline, these genes were similar in prevalence in both groups of children and increased by 60 days, irrespective of the treatment received. Data on the prevalence of macrolide resistance in children in Botswana is limited; however, a recent study of wastewater found high levels of resistant bacteria in the environment (38). Although the abundance of certain erm genes changed more dramatically in one treatment group compared to the other, there is large individual variability within each group that may have skewed the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline, these genes were similar in prevalence in both groups of children and increased by 60 days, irrespective of the treatment received. Data on the prevalence of macrolide resistance in children in Botswana is limited; however, a recent study of wastewater found high levels of resistant bacteria in the environment (38). Although the abundance of certain erm genes changed more dramatically in one treatment group compared to the other, there is large individual variability within each group that may have skewed the results.…”
Section: Discussionmentioning
confidence: 99%
“…What is concerning, however, is the association of this macrolide phosphotransferase with IS elements. Plasmids containing mphA have been identified in ETEC isolates and are common in bacteria circulating in wastewater and river environments in Botswana (38,39).…”
Section: Discussionmentioning
confidence: 99%